Electrical Properties and Optimum Conditions of A Home-Made Magnetron Plasma Sputtering System - Hassan, Sarah Ahmed; Anber, Ahmed Abed; Abdullah, Eidan Asi; Odah, Jafer Fahdel; Jubier, Najwa J.; Abd Alwahab, Ali Adnan (Iraqi Journal of Science, 2021)
In this work, the electrical properties and optimum conditions of the plasma sputtering system have been studied. The electrical properties such as Paschen's curve, current-voltage, current pressure relations, the strength of magnetic field as a function of inter-electrode distance, the influence of gas working pressure and argon-oxygen ratio on the electrical characterization were studied to determine the basic optimum condition of the system operation. the discharge current as a function of discharge voltage showed high discharge current at 2.5 cm. These parameters represent the basic conditions to operate any plasma sputtering system which are the right behavior to build up and design the discharge an electrode. The ideal conditions of these homemade systems were qualified to prepare the various nanostructure thin films. The two electrodes were made of copper because of its good conductivity, and to avoid the power dissipation inside discharge chamber.